Accounting treatment of cryptocurrency: a Malaysian context / Teh Sin Yee, Angeline Yap Kiew Heong and Wong Siew Chin - Teh, Sin Yee; Yap, Angeline Kiew Heong; Wong, Siew Chin (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
Cryptocurrencies have become the buzzword among society, especially after some prominent companies such as Wikipedia, Microsoft and Amazon accept the use of cryptocurrencies. Nonetheless, accounting treatment of cryptocurrencies appears to be a challenging area for standard setters, financial statement preparers, and also users. This is mainly because elements of cryptocurrency do not explicitly fall under any existing accounting standards. The fact that cryptocurrencies are held for different business models and intentions may affect how it should be treated under accounting standards. Hence, this research aimed to examine factors that affect the accounting treatment of cryptocurrencies in Malaysia. Different factors were examined including the function of cryptocurrencies, conceptual framework of financial reporting and the legal status of cryptocurrencies. Targeted respondents involved in this research were accountants in Malaysia. Data collected were analysed using SPSS and SmartPLS 3. SPSS was mainly used to analyse the demographics of respondents whereas SmartPLS 3 was used to carry out reflective measurement model and structural model evaluation. The results concluded that all the independent variables which are the functions of cryptocurrencies, conceptual framework of financial reporting, and the legal status of cryptocurrencies have a significant relationship with the accounting treatment of cryptocurrencies. The results of this study provide an insight about factors that standards setters and financial standards should consider when accounting for cryptocurrencies' transactions in order to provide faithful representation and relevant information. Some limitations and suggestions are included in this research to provide ideas for future researchers to carry out further research.